STORING THE GASOLINE THE CONSTRUCTION OF INTRA-ETHNIC AND INTER-ETHNIC CIRMUSTANCES Building Peace and Constructing Conflict in Civil Society - Andini, Batari Oja (JPP (Jurnal Politik Profetik), 2017)
This paper is aimed to find the cause of conflict in civil society by exploring the concept of intra-ethnic and inter-ethnic society offered by Ashutosh Varshney. According to Varshney, intra-ethnic engagement would lead the society to ethnic violence. On the contrary, inter-ethnic engagement would lead society to ethnic peace. This paper will show that inter-ethnic and intra-ethnic engagementsare impermanent circumstances, which are constructed by society. The inter-ethnic and intra-ethnic circumstances could be conducted by performing or not performing the symbols of each ethnic group. The example mentioned in this paper is the interaction between two religious-ethnic groups, namely; Buddhist-Tionghoa and Christian-Torajan. The data of the example were gained by doing qualitative fieldwork, particularly participatory observation.